Disrupted water governance in the shadows: Revealing the role of hidden actors in the Upper Cauca River Basin in Colombia - Figueroa-Benitez, Alejandro; Nagheeby, Mohsen; Figueroa, Apolinar; Amezaga, Jaime (Frontiers in Water, 2023)
Colombia's policy in the Upper Cauca River Basin is diminished by a lack of legitimacy in local areas respecting the control of territory and water. Such illegitimate interference provides a hiding place and fertile ground for the illegal activities of “hidden” actors. This paper aims to scrutinize the potential power of such hidden actors to influence water governance. We engage with critical discussions of water governance to reveal the role of these actors in controlling territory and water in the Upper Cauca River Basin. Extensive fieldwork was carried out, including workshops, interviews, and informal talks. Despite the Colombian government not recognizing hidden actors and their part in influencing water-related policies, the information gathered revealed their active agency in the basin. The paper shows how these actors play a determining role in territorial development and water resource management, disrupting the functioning of the State's water governance. Hidden actors, to promote their own, mostly illegal and illegitimate businesses, seize upon the current lack of clarity in the national normative standards, the deficiencies created by an inconsiderate implementation of national water policy, and the State's lack of legitimacy at the local level. This paper concludes that the awareness of hidden actors and their invisible power over water governance provide a better sense of the reality on the ground for policymakers in Colombia.